Adherence, persistence and efficacy of dasatinib and nilotinib in the treatment of patients resistant or intolerant to imatinib with chronic myeloid leukemia in chronic phase: an Italian multicenter study over two years in real life. (4th March 2021) - Santoleri, Fiorenzo; Ranucci, Elena; La Barba, Gaetano; Colasanto, Irene; Scaldaferri, Matilde; Cattel, Francesco; Federici, Francesca; Rossi, Chiara; Di Biagio, Katiuscia; Scortechini, Anna Rita; Musicco, Felice; Torquati, Giancarlo; et al.
Abstract: Background: The use of dasatinib and nilotinib in the treatment of patients with chronic myeloid leukemia represents a valid therapeutic option for patients resistant or intolerant to imatinib. In this multicentre study, adherence, persistence and efficacy in real life over two years of treatment were evaluated. Materials and methods: Adherence to treatment was calculated as the ratio between the dose received and the prescribed dose. The dose received was calculated using pharmacy refill data. The persistence with treatment was calculated as the difference between the end and the beginning of the treatment. Efficacy was assigned as Progression-Free Survival (PFS) and Events-Free Survival (EFS) and represented through the Kaplan-Meier curve. Results: The number of patients analysed was 117, 70 treated with dasatinib and 47 with nilotinib. Adherence to treatment for dasatinib and nilotinib at two years was 0.91 and 0.82 respectively. Persistence at two years was 77% while the PFS was 92% for both drugs in the study. Conclusion: Adherence to the treatment calculated over two years showed a superiority of dasatinib over nilotinib. Nevertheless, the efficacy in terms of PFS and EFS is superimposable between the two drugs in the study.